HUBUNGAN ANTARA POLA MAKAN DENGAN STATUS GIZI BALITA DI DAERAH TRANSMIGRASI RING I TRISIK, PANTAI SELATAN KULONPROGO - Fitri Dian Kurniati (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2017)
Background: Children under five years old, in a period of their growth, are represent group which is influenced by existence of the change intake consume food. The cause of children under five years old who have lacked of nutrition are generally they lacked of intake food, they often sick or they have infection. The aims of this study is to know the correlation between eat pattern with nutrition status of children under five years old in transmigration area of ring I Trisik, South Coastal of Kulonprogo.Methods: This research was a descriptive research with cross-sectional design. This Research represent analytic descriptive research with device of cross sectional. The subject of this research consist of children under five years old in transmigration area of ring I Trisik, South Coastal of Kulonprogo. The data was taken by total sampling (n=30). The data were collected through observation weight of children under five years old and distributed questioner about eat pattern to respondent.Result: The finding of the research show that children under five years old who have proper eat pattern can be classified into 17 children under five years old (56,67%), 12 children under five years old (40%) having enough eat pattern, and only 1 children under five years old (3,33%) having lack of eat pattern. Most of the children under five years old have proper nutrition status with 22 children under five years old (73,33%) and 8 children under five years old (26,67%) having lack of nutrition status. The result of chi square test that relates between eat pattern with children under five years old is 0.001 for p value.Conclusion: There is a significance relationship between eat pattern and nutrition status of children under five years old in transmigration area of ring I Trisik, South Coastal of Kulonprogo